A sewing needle in the liver in children: A case report and literature review. Issue 27 (8th July 2022) - Xing, Huiwu; Tan, Bingqian; Yang, Chenyu; Zhang, Mingman
Abstract : Rationale: In clinical practice, foreign bodies (FBs) in the digestive tract are more common in children, but intrahepatic FBs are rare, especially those that can cause infection, bleeding, bile leakage, and other complications. However, there is no consensus on its diagnosis and treatment due to the lack of large-scale cohort studies. Patient concerns: Case 1 is a 4-years 8-months-old girl, who at the age of 10 months, showed an X-ray finding of a striped FB in her liver, with no symptoms. However, the patient's parents refused surgery. After nearly 4 years of active surveillance, the patient visited our hospital for surgery. Case 2, a 2-year-old male, reported a sewing needle that completely pierced into the right upper abdomen due to an accidental fall that took place half-a-day before admission. He only had right upper abdominal pain. CT showed a striped FB in the liver. Diagnosis: FB in the liver (sewing needle). Interventions: Both the patients were injected with human tetanus immunoglobulin and underwent surgical removal. Outcomes: Both patients recovered smoothly and had no complications during follow-up. Lessons: Active surveillance might be considered for cases with no symptoms or complications and no displacement of the FB, but surgery should be the first choice. If the patient's condition is complicated, it is recommended to use ultrasound or X-ray to help decision-making during the operation. Additionally, tetanus, child safety, and family education are important supportive measures.